Types and classification of digital assets: legal aspect - Zhaksylykbayeva Ә.А.; Suleimenova С.Ж.; Aldabergenova Н.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The digital economy has changed the way values are created, stored and transmitted. As a result, a wide variety of digital assets have emerged, each with unique characteristics and capabilities. The paper explores different types of digital assets, from cryptocurrencies and stablecoins to irreplaceable tokens (NFT) and central bank digital currencies (CBDC), highlighting their technological fundamentals, economic role and legal differences. By understanding the different categories of digital assets, we can assess the opportunities and challenges they present in the modern digital age. This article aims to consider the classification of digital assets from a scientific (technological and structural) and legal (ownership and regulation) perspective, with an in-depth analysis of the categories that have emerged in recent years. It also explores how different legal structures in jurisdictions such as Kazakhstan, the European Union (EU) and the United States (USA) are evolving to manage these new forms of value exchange. The scientific novelty of the research lies in the development of the author’s classification of digital assets based on their technological and legal characteristics. The practical significance of the work lies in the possibility of using the results obtained in improving legislation, law enforcement practice and the development of regulatory approaches in the field of digital assets.